أساليب تعليم مهارات الكلام في تعليم اللغة العربية (دراسة تحليلية على كتاب "العربية بين يديك"): Techniques for Teaching Speaking Skills in Teaching Arabic (Analysis of the Book of al-`Arabiyyah Baina Yadaik fī Ta`Līm al-Lugah al-`Arabiyyah lī Gairi al-Nāṭiqina Bihā) - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2022)
This study aims to describe the techniques of teaching speaking skills from the book of al-Arabiyyah Baina Yadaik fī Ta'līm al-Lugah al-Arabiyyah li Gairi al-Nātiqīna Bihā. This type of research is descriptive qualitative research using content analysis methods and literature study in data collection. The results of this study indicate that the book of al-Arabiyyah Baina Yadaika is a good textbook in presenting speaking skills teaching techniques for foreign speakers. This is found in the following points: (1) this book uses the technique of “Listening to the Text” using untranslated Arabic; (2) this book uses the “Understanding of the Text” technique to determine the extent to which students understand the text; (3) this book uses the technique of “Imitating and Repeating” in teaching speaking skills to form habits for learners in language; (4) this book uses the technique of "Teaching Letters Pronunciation" with its three elements in order to correctly pronounce letters and words; (5) this book uses the technique of “Picture Vocabulary Teaching” which aims to teach speaking skills by direct method; and (6) this book uses the “Communication” technique because the basic goal in language teaching is communication.